Internal displacement beyond 2018: the road ahead - Bilak, A (Refugee Studies Centre, University of Oxford, 2018)
The statistics and the challenges around internal displacement are daunting. However, much has been learned since the Guiding Principles on Internal Displacement were launched in 1998. What is needed now is a concerted effort and sustained momentum to build on that awareness and meet the evolving challenges.